The Responsibility of Family Maintenance by Drug Users: An Islamic Family Law Perspective (Case Study at Polres Kepahiang) - Eka Gustian Saputra; Yusefri Yusefri; Aida Rahmi Nasution; Rifanto Bin Ridwan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze two main issues. First, how family maintenance (nafkah) is fulfilled by drug users who are heads of households during the law enforcement process at the Kepahiang Resort Police (Polres Kepahiang). Second, how Islamic family law reviews the fulfillment of such maintenance within the legal jurisdiction of Polres Kepahiang. This study employs an empirical juridical method with a qualitative approach, combining the analysis of Islamic legal norms with empirical facts in the field. Data were obtained through in-depth interviews with law enforcement officers, families of drug users, and community leaders. The results show that the detention process for drug users has a significant impact on family economy. All informants (100%) working in the informal sector lost their primary source of income, resulting in difficulties in meeting food needs (100%), delays in children's education costs (60%), limited access to healthcare (40%), debt burdens (80%), and even the threat of school dropout (20%). From the perspective of Islamic Family Law, a husband's obligation to provide maintenance does not lapse even during detention. However, detention can be categorized as a uzur syar'i (legally recognized constraint) that causes the postponement of this obligation (muwassa') due to physical incapacity to work, in accordance with the Islamic legal maxim